Soil and Groundwater Characteristics of a Legacy Spill Site - A Adoki (Journal of Applied Sciences and Environmental Management)
The soil and groundwater of a legacy spill site in Eleme Local Government Authority Area of Rivers Stae were investigated. The general land use of the area within 1500m radius of the spill site is devoted to farming, fishing and hunting. The main crops grown include yams, cassava, maize, sugarcane, plantain, banana, oil palm, coconut, raffia palm. Families own the land and this ownership is by inheritance. In recent times, people can purchase land for use and others can also hire. The stratigraphy of the subsurface at the study site is closely related to the local geology of the site. Basically, the local geology is that of the coastal plains sands. Generally, the water table at the study area ranges from a low of 0.0m (at ground surface) to a high of about 5.10m. Where it occurs within the subsurface, the groundwater was observed to occur either within the lower part of the sandy clay or within the sands and gravels layer. The general direction of the groundwater flow within the area was observed to be from the North West to the South East. Underground pollution plumes were also in this general direction with possible local variations as dictated by the variations in subsurface lithography from point to point. The potential sources of contamination were: The primary Source of contamination at the study site were the stock piles of excavated surface material deposited at the site; Past accidental leak of crude oil from the 28” pipeline that passes through the western site boundary of the location. The secondary sources were impacted surficial and subsurface Soils (Trial Pits: TP1, TP3, TP5, TP9, TP13, TP15, TP17 and TP21) and Impacted Groundwater (Boreholes: BH1 to BH10); Dissolved Surface Water (Surface Water SW1 to SW6). The chemicals of potential concern (COPCs) are Total Petroleum Hydrocarbons and Heavy metals (chromium and lead). JASEM